The Gnostic Vol. 02, No. 13, July 1888 - Chainey, George; Kimball, Anna (My University, 1888)
The Gnostic (George Chainey and Anna Kimball) 1, no. 11 [i.e. 2, no. 13](July 1888). Individual Archives – Periodicals G-N. New Age Movements, Occultism and Spiritualism Research Library. Valdosta State University. https://hdl.handle.net/10428/5022
1 Electronic record(s). 34 pages and image scans.
Keywords: Periodicals; Gnosticism; Occultism; Spiritualism; Theosophy